Overview of Genetic Diagnosis in Cancer. (6th April 2017) - Korf, Bruce R.; Mikhail, Fady M.
Abstract: Both cytogenetic and molecular genetic studies can contribute to the management of patients with cancer. In some cases, genetic markers are specific to particular tumor types and are useful in diagnosis. This can be helpful in distinguishing histologically similar tumors that may respond differently to treatment and can sometimes be of prognostic value. Genetic markers can also be tools for following the response of a tumor to therapy, providing a sensitive means to detect relapse. This introductory unit considers some of the types of genetic changes that occur in association with malignancies, as well as major approaches used in their detection. © 2017 by John Wiley & Sons, Inc.